1959
DOI: 10.1037/h0083787
|View full text |Cite
|
Sign up to set email alerts
|

Motivational variables in second-language acquisition.

Abstract: MOST BESEABCH on second-language acquisition has been concerned with the measurement of an "ability for languages," the assumption being that achievement is largely due to a linguistic aptitude. However, when measures of aptitude are correlated with grades in language courses, the validity coefficients show considerable variability from situation to situation even with tests developed through factor analytic methods (2), suggesting that variables other than linguistic aptitude are involved. Researchers have me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
715
3
51

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,106 publications
(790 citation statements)
references
References 38 publications
21
715
3
51
Order By: Relevance
“…Chamber ( 1999 ) found that learning is better achieved when the learner has a positive approach towards the language and the learning process. Furthermore, Gardner and Lambert (1972) in their broad study provide evidence that positive outlooks toward learning a language enhance proficiency as well. Hence, the significance of this study lies in demonstrating the effect of gender on the students' willingness to learn, and their expectation in association with a teacher's gender.…”
Section: Gender Dynamics In the Classroommentioning
confidence: 99%
“…Chamber ( 1999 ) found that learning is better achieved when the learner has a positive approach towards the language and the learning process. Furthermore, Gardner and Lambert (1972) in their broad study provide evidence that positive outlooks toward learning a language enhance proficiency as well. Hence, the significance of this study lies in demonstrating the effect of gender on the students' willingness to learn, and their expectation in association with a teacher's gender.…”
Section: Gender Dynamics In the Classroommentioning
confidence: 99%
“…Their attitudes can have impact on the language proficiency level that they intend to achieve (Gardner, Moorcroft, & Metforda, 1989). Learners with positive attitudes are more likely to achieve better success than those with negative attitudes towards the learning of the L2 language (Dörnyei, 1994;Feenstra, 1967;Gardner, 1960;Gardner & Lambert, 1959;Lambert, Gardner, Olton, & Tunstall, 1968;Svanes, 1988). When their attitudes are positive, they are more inclined to become motivated to learn the language and accordingly more willing to dedicate more time and effort to the learning endeavor (Culhane, 2004;Gardner, 1968;Gardner, Masgoret, & Tremblay, 1999), as well as more behaviourally, cognitively, and affectively engaged in learning the L2 (Gardner, 2007).…”
Section: Learner Attitudes and L2 Acquisitionmentioning
confidence: 99%
“…Gardner & Lambert 1959, 1972, have been transposed to the area of language attrition; Gardner (1982:31-32) argues: "(...), since attitudinal/motivational characteristics are related to the level of second language proficiency, they will relate to second language retention (...). The model proposed argues that attitudinal variables involving integrativeness and the learning situation influence and maintain levels of motivation which, in turn, effect differences in second language proficiency (...).…”
Section: Fl Attritionmentioning
confidence: 99%